Experiences of being screened for intimate partner violence during pregnancy: a qualitative study of women in Japan - Yaeko Kataoka; Mikiko Imazeki (BMC, 2018)
Abstract Background Intimate partner violence (IPV) is physical, sexual or psychological violence by a current or former intimate partner. IPV threatens women's health, and during pregnancy women are more vulnerable to violence. Therefore, IPV screening has been recommended during antenatal care; however, health care providers have expressed concern about the negative impact on women and therefore have been reluctant in conducting IPV screening. Consequently our objective was to investigate pregnant women's experiences of reading and completing an IPV screening questionnaire. Methods Semi-structured interviews were conducted with postpartum women who had received IPV screening during pregnancy to investigate their experiences using the IVP Violence Against Women Screen (VAWS). Qualitative data were analyzed based on content analysis. Results A total of 43 women participated in this study. There were eight (18.6%) women positive for IPV screening during pregnancy. Content analysis for all participants revealed three themes: necessity, acceptability and optimality. 'Necessity' referred to benefits for women from IPV screening, and was supported by three categories: 'redefining the relationship', 'promoting IPV awareness' and 'opportunity to initiate support'. 'Acceptability' of IPV screening was also supported by three categories: 'comfortable', 'quickly completed' and 'difficulty'. 'Optimality' meant IPV screening during pregnancy was appropriate timing for women who had been screened as either positive or negative. Conclusions The majority of women, including women experiencing IPV, had positive responses to IPV screening during pregnancy. Future diffusion of IPV screening requires safe environments for IPV screening and improved awareness of health care providers towards IPV.